Effect of Fructose and 3,5-Diiodothyronine (3,5-T2) on Lipid Accumulation and Insulin Signalling in Non-Alcoholic Fatty Liver Disease (NAFLD)-Like Rat Primary Hepatocytes - Gnocchi, D.; Massimi, M.; Alisi, A.; Incerpi, S.; Bruscalupi, G. (Hormone and Metabolic Research, 2014)
Non-alcoholic fatty liver disease (NAFLD) is nowadays considered as one of the most serious pathological conditions affecting the liver. NAFLD is supposed to be initiated by the accumulation of lipids in the liver, which finally results in an impaired hepatic insulin signalling. Many researchers have recently focused their attention on the role played by fructose as a NAFLD-triggering agent, because of the increased diffusion of fructose-sweetened food. However, epidemiological data do not permit to evaluate the role of fructose per se, because these foods are often associated with elevated energy intake and unhealthy lifestyle. In the present work, we analysed the effects of fructose on the accumulation of lipids and insulin signalling in rat primary hepatocytes. Moreover, we investigated the effect of the thyroid hormone metabolite, devoid of thyrotoxic effects, 3,5-diiodothyronine (3,5-T2) over the same parameters. To evaluate the effect on insulin signalling we took into consideration three key proteins, such as p85 subunit of phosphatidylinositol 3-kinase (PI3K), phosphatase and tensin homolog (PTEN), and Akt. Our results show that fructose in vitro, in the range of physiological concentrations, was not able to stimulate either lipid accumulation or to impair insulin signalling in our NAFLD-like rat primary hepatocytes. Our data thus support the idea that fructose per se may exert detrimental effects mainly triggering systemic effects, rather than directly affecting isolated hepatocytes. Moreover, we demonstrated that 3,5-T2, at physiological levels, reduces lipid content and triggers phosphorylation of Akt in an insulin receptor-independent manner, revealing new interesting properties as a biologically active molecule.
Keywords: insulin signal transduction; Akt; p85; PTEN